i-WARM: Development of a Board Examination Reviewer Web Application for Filipino Pre-Service Physical Educators Utilizing the Unified Spaced Repetition and Hypercorrection Techniques - Almario, John Ivan F.; Quiambao, Angel S.; Sangalang, Algenrev M.; Manlutac, Abigail M.; Tolentino, Julius Ceazar G.; Miranda, John Paul P. (Multidisciplinary journal for education, social and technological sciences, 2024)
One of the major parameters by which college graduates' productivity is gauged is their board examination performance. Relevantly, the development and utilization of sophisticated tools and technology to facilitate reviews are encouraged and worthy of such exploration. The study aimed to develop an integrated web application reviewer for MAPEH (music, arts, physical education, and health) (i-WARM) with the use of unified spaced repetition and hypercorrection techniques. This descriptive research and development (R & D) design was used and employed a nine-step process in which functions were built for effective learning and retention of concepts. The evaluation was conducted by 106 graduating Bachelor of Physical Education students from a teacher education institution in Central Luzon, Philippines. Results revealed that the i-WARM is easy to use and easy to learn as it was viewed as clear and understandable, accessible, and has a flexible feature and interface. Pre-service physical educators perceived that the services provided by the web application are useful for their review as it was rated functional and informative. Frequent problems such as crashes and downtimes were not observed by the user during their exposure to the web application. The i-WARM could be explored as a potential aid in assisting learners to acquire concepts easily through an interactive interface. This may likewise assist teachers and students in establishing retention of significant concepts for future licensure examinations.